Challenges faced by the small and medium enterprises (SMEs) in Malaysia : an intellectual capital perspective - Mohammad Khalique, Muhd Sadique; Abu Hassan, Md. Isa; Jamal Abdul, Nassir Shaari; Adel, Ageel (Academic Journals, 2011)
In a knowledge based economy the role of small and medium enterprises is very critical for the economic development. The main thrust of this study was on the competiveness of the SMEs in a knowledge-based economy. In addition, this study also explores the challenges which are facing the small and medium enterprises (SMEs) in Malaysia. The significance of the study will add the knowledge about the current issues relating with SMEs in Malaysia in intellectual capital perspective.